The Prophetic Year and Its Role in Achieving Sustainable Development in the Conservation of Water ResourcesAn Inductive Descriptive Study - Alwan, Prof. Dr. Safaa Jaafar Alwan; Jawad, Prof. Dr. Saadoun Muhammad Jawad (Sulaimani Journal for Humanities, 2026)
The research addressed a vital and renewable topic in every time and place in preserving water resources through the prophetic hadiths that came in their folds what urges and clarifies in multiple images in preserving them by not being extravagant in using them in all areas that society needs، and contributing to their cleanliness and not polluting them، as it is one of the basic environmental elements that societies need in the continuity of life in them، and then achieving sustainable development in them، after applying it practically، so we wanted in this research to show the aspects that the Sunnah of the Prophet guided us and urged us to in sayings، actions and reports in the necessity of preserving water resources، and achieving their sustainable development for the urgent need for them in worldly life، so the research was divided into two topics: The first topic: Clarifying the concept of the Sunnah of the Prophet، sustainable development and water resources in language and terminology، and it contains three demands: The first demand: The concept of the Sunnah of the Prophet in language and terminology، and clarifying the concept of the Sunnah of the Prophet، and the second demand: The concept of sustainable development in language and terminology، and clarifying the concept of sustainable development، the demand Third: Explaining the concept of water resources
Keywords: 1 The Prophetic Sunnah 2 Development 3 Sustainable 4 Water Resources 5 Basic Environment